The Business Models of Frugal Enterprises for Sustainable Development in a Constrained Environment - Mokter Hossain (14634969) (2024)
Constraints and institutional voids in emerging markets pose significant challenges to serving low-income customers. Indeed, the complex constraints often discourage traditional companies from pursuing such endeavors, but a new breed of enterprises characterized by their frugal approach is emerging from this constrained environment. Nevertheless, we know little about how these frugal enterprises transform constraints into opportunities through innovative business models that include collaboration with local and international partners, as well as how they can contribute to sustainable development. Drawing on institutional theory perspective and the resource-based view, this article explores how frugal enterprises create business models for serving overlooked customers in emerging markets and overcoming the various constraints and institutional voids. Based on six cases of frugal enterprise and 22 interviews, this qualitative study contributes to the literature in the following three ways. First, it reveals how frugal enterprises transform constraints and institutional voids into viable business models for serving traditionally underserved customers. Second, it sheds light on how these enterprises engage with local and international partners to overcome the constraints in emerging markets. Finally, it demonstrates that frugal enterprises contribute to sustainable development in a profitable manner. The findings offer valuable insights to guide managers and policymakers in attaining sustainability and profitability in the emerging markets. Other Information Published in: IEEE Transactions on Engineering Management License: Ihttps://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1109/tem.2023.3342440